UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA CD PEMBELAJARAN DISERTAI PEMBERIAN TUGAS PADA SISWA KELAS VII SMP NEGERI 1 BANJAR MARGO - Sumbogo B M (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
This research is a class action (classroom action research). The aims this research is to determine whether the use of CD learning about triangles and rectangles can increase the activity of students and student learning outcomes class VII.7 SMP Negeri 1 Banjar Margo in the academic year 2015/2016. Based on the analysis, obtained an average student activity before the action amounted to 42.53%, the average student activity first cycle of 65.33% and the average student activity cycle II 74.00%. Means the average activity of students has increased by 15.7%. The average results of student learning the first cycle of 56.7 and an average student learning outcomes cycle II of 65.3, an average of learning outcomes increased by 15.2%. Before remedial many students who pass the study in the first cycle of 16 students (53.3%), it increased 5 students (16.7%) from the prior action. And the second cycle students who pass the study were 21 students (70.0%), it increased 5 students (16.7%) of the cycle I. Based on the results of classroom action research conducted and the discussions that have been described, it can be concluded that the use of CD Lesson in Math learning materials triangles and rectangles can increase the activity and student learning outcomes VII.1 grade SMPN 1 Banjar Margo, Tulang Bawang in the academic year 2015/2016.